International Financial Integration and Funding Risks : Bank-Level Evidence from Latin America - Catao, Luis (IMF Working Papers; Working Paper ;, 2017)
Using a sample of over 700 banks in Latin America, we show that international financial liberalization lowers bank capital ratios and increases the shares of short-term funding. Following liberalization, large banks substitute interbank borrowing for equity and long-term funding, whereas small banks increase the proportions of retail funding in their liabilities, which have been particularly vulnerable to flight-to-quality during periods of financial distress in much of Latin America. We also find evidence that riskier bank funding in the aftermath of financial liberalizations is exacerbated by asymmetric information, which rises on geographical distance and the opacity of balance sheets.